Changes in the herbicide tolerance of maize genotypes in wet and dry years - Bónis, Péter; Árendás, Tamás; Berzsenyi, Zoltán; Marton, Csaba L. (Acta Agraria Debreceniensis, 2011)
The tolerance of 15 inbred maize lines grown on chernozem soil with forest residues in Martonvásár was tested against herbicides applied post-emergence in two dry, warm years (2003 and 2011) and in two cool, wet years (2004 and 2010). The herbicides mesotrione + terbutylazine, nicosulfuron and dicamba were applied to maize inbred lines in the 7–8-leaf stage at the maximum dose authorised for practical use and at double this rate. The plants were scored for the intensity of visible phytotoxic symptoms 14 days after treatment.The level of phytotoxicity observed in dry, warm years was 5.14%, averaged over the lines, herbicides and rates. The intensity of visible symptoms was almost 2.5 times as great in cool, wet years (12.76 %).Averaged over the four years, the lines and the rates, the least damage was caused by dicamba (5.77 %), followed by mesotrione + terbutylazine (7.23 %). The most severe symptoms were induced by nicosulfuron (16.17 %). This could be attributed to the fact that some of the inbred lines were extremely sensitive to herbicides, especially those of the sulfonylurea type.A difference of more than 1.5 times was observed between the two doses, but the correlation between the concentration and the severity of the visual symptoms was not strictly linear. Compared to the normal dose (100 %) the double rate resulted in a 162.5% increase in symptom severity. In most cases plants treated with the normal dose were symptom-free or only exhibited a low level of phytotoxicity.